Continuous technological and behavioral development of late Pleistocene hominins in central South China: Multidisciplinary analysis at Sandinggai. (15th December 2022) - Li, Hao; Li, Yiyuan; Yu, Lupeng; Tu, Hua; Zhang, Yuzhu; Sumner, Alexandra; Kuman, Kathleen
Abstract: Lithic technological development in the Late Pleistocene of South China has received substantial attention in recent years due to a series of recent fossil discoveries in the region, including some assigned to early modern Homo sapiens . Here we present a comprehensive study of the open-air site of Sandinggai, which is located in the middle valley of the Yangtze River in central South China. Luminescence dating based on quartz and feldspar has shown that the initial occupation of the site began from ca. 96.6 ± 5.1 ka and continued until the end of the last deglacial period (i.e., ca. 13.3 ± 0.3 ka). The site thus provides a substantial chronological sequence to investigate the behavioral development of early humans. Technological analysis shows that a Large Cutting Tool (LCT) techno-complex based mainly on coarse-grained quartz sandstone co-existed with a small flake and flake tool production system based on chert, with the latter playing a more prominent role. In addition, this small débitage flaking component lacks skillful prepared core technology, which is often present in the West at contemporaneous sites. Furthermore, from a wider regional context, an evolutionary pattern is suggested which shows that the pre-existing Middle Pleistocene LCT techno-complex underwent a marked decline during the Late Pleistocene, while in contrast, the local small flaking system became prominent and continued to develop through time, without discernible external influence. These data suggest a re-evaluation of current ideas on the movement of early modern humans into the region, along with their potential influence in the different regions of South China. Highlights: Site occupation began from ca. 96.6 ± 5.1 ka and continued to the last deglaciation. Pre-existing Middle Pleistocene LCT techno-complex underwent a marked decline. Local small flaking system became prominent and continued to develop through time. Re-evaluation of current ideas on the emergence of H. sapiens in South China.